Contribuição do uso de medicamentos para a admissão hospitalar - Mastroianni, Patricia de Carvalho [UNESP]; Varallo, Fabiana Rossi [UNESP]; Barg, Marina Souza [UNESP]; Noto, Ana Regina [UNESP]; Galduróz, José Carlos Fernandez [UNESP] (FapUNIFESP (SciELO), 2009)
According to the Word Health Organization, adverse drug reactions (ADR) are any harmful and non intentional answer which occurred in doses normally used in human beings. The ADR can be responsible for 2.4% to 11.5% of hospital admissions. Therefore, this study aimed at knowing the admitted patient's demographic profile due to possible ADR, identifying the most frequent drugs and complaints, and evaluating the incidence of hospital admission related to drug use. Patients who were 18 years old or more and were admitted during a period of one month to a medical clinical of a general hospital were interviewed for one month about drug use before being admitted, as well as regarding to the complaint which led them to hospital. These information were analyzed according to official data, like MICROMEDEX® and WHO criteria as well. It was observed that the admission due to drug use occurred in most part of the cases in elderly [47.5% (66/139)] and women [62% (87/139)]. The most frequent drugs used were: omeprazole (16), analgesics (31), antihypertensive (31), simvastatin (7) and formoterol fumarate (6), and the symptoms were normally associated to the digestive (20.5%), circulatory (20.2%), respiratory (18.2%) and central nervous systems (13.9%). It was estimated that 15.5% (139/897) of the hospital admission occurred possibly due to the drug use. The data found by present study suggests some strategies in order to prevent ADR in the context of primary health care services, such as monitoring drug therapy, manly for patients with chronic diseases, elderly and polimedicated people; and pharmaceutical care including dispensation and purchasing of the drugs, a lot of them dispensed over the counter (OTC).
Contribution of the use of drugs for hospital admission
Keywords: Drugs/adverse reactions; Drugs/rational use; Pharmaceutical attention; Pharmacotherapeutic care; acetylsalicylic acid; amiodarone; analgesic agent; antihypertensive agent; atenolol; captopril; dipyrone; enalapril; formoterol; formoterol fumarate; non prescription drug; omeprazole; paracetamol; simvastatin; adult; age distribution; arterial pressure; asthma; bronchospasm; chronic disease; congestive heart failure; data analysis; demography; diabetes mellitus; drug use; dyspnea; female; fever; gastrointestinal disease; gastrointestinal symptom; headache; heart beat; heart infarction; hospitalization; human; kidney failure; major clinical study; male; mucosa inflammation; muscle disease; myalgia; nausea; osteoarthritis; patient monitoring; pharmaceutical care; pneumonia; primary health care; rash; sex ratio; side effect; somnolence; symptom; urine retention; vomiting; world health organization